Formate and hydrogen in hydrothermal vents and their use by extremely thermophilic methanogens and heterotrophs - Holden, James F.; Sistu, Harita (Frontiers in Microbiology, 2023)
Extremely thermophilic methanogens in the Methanococci and heterotrophs in the Thermococci are common in deep-sea hydrothermal vents. All Methanococci use H2 as an electron donor, and a few species can also use formate. Most Methanococci have a coenzyme F420-reducing formate dehydrogenase. All Thermococci reduce S0 but have hydrogenases and produce H2 in the absence of S0. Some Thermococci have formate hydrogenlyase (Fhl) that reversibly converts H2 and CO2 to formate or an NAD(P)+-reducing formate dehydrogenase (Nfd). Questions remain if Methanococci or Thermococci use or produce formate in nature, why only certain species can grow on or produce formate, and what the physiological role of formate is? Formate forms abiotically in hydrothermal fluids through chemical equilibrium with primarily H2, CO2, and CO and is strongly dependent upon H2 concentration, pH, and temperature. Formate concentrations are highest in hydrothermal fluids where H2 concentrations are also high, such as in ultramafic systems where serpentinization reactions occur. In nature, Methanococci are likely to use formate as an electron donor when H2 is limiting. Thermococci with Fhl likely convert H2 and CO2 to formate when H2 concentrations become inhibitory for growth. They are unlikely to grow on formate in nature unless formate is more abundant than H2 in the environment. Nearly all Methanococci and Thermococci have a gene for at least one formate dehydrogenase catalytic subunit, which may be used to provide free formate for de novo purine biosynthesis. However, only species with a membrane-bound formate transporter can grow on or secrete formate. Interspecies H2 transfer occurs between Thermococci and Methanococci. This and putative interspecies formate transfer may support Methanococci in low H2 environments, which in turn may prevent growth inhibition of Thermococci by its own H2. Future research directions include understanding when, where, and how formate is used and produced by these organisms in nature, and how transcription of Thermococci genes encoding formate-related enzymes are regulated.